Pulsed plasmachemistry of COx, NOx, SOx - Berezina, G.P.; Onishchenko, I.N.; Us, V.S. (Вопросы атомной науки и техники, 2000)
The pulsed spark discharge at atmosphere pressure has been considered as a suitable tool for plasma chemistry of COx, NOx, and SOx. The multi-spark electric discharge, “dancing” between a set of eagles and a plate was used for the treatment of a considerable gas volume. The theoretical and experimental investigations have been performed to dissociate the gases mentioned above. In particular the percentage of COx dissociation above 30% has been achieved in accordance with the theoretical evaluations.